2015
DOI: 10.1103/physreve.91.012923
|View full text |Cite
|
Sign up to set email alerts
|

Classical billiards and quantum fluids

Abstract: The dynamics of a particle confined in the elliptical stadium billiard with rectangular thickness 2t, major axis 2a, and minor axis 2b=2 is numerically investigated in a reduced phase space with discrete time n. Both relative measure r(n), with asymptotic value r(n→∞)=r(∞) and Shannon entropy s, are calculated in the vicinity of a particular line in the a×t parameter space, namely t(c)=t(0)(a)=√a(2)-1, with a∈(1,√4/3). If t Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The ergodic property (ρ c = 1) is numerically guaranteed in black regions. This diagram also supports previous works [28,29], where a critical transition from a mixed phase space to a fully ergodic was found to cross a critical line t(a) = √ a 2 − 1. The E-C 3 B's classical dynamical properties will be studied in the same way but are characterized through the collisions of the orbits with the horizontal side of its FD shown in Fig.…”
Section: The Bi-parametric Billiards Families and Classical Dynamicssupporting
confidence: 91%
See 4 more Smart Citations
“…The ergodic property (ρ c = 1) is numerically guaranteed in black regions. This diagram also supports previous works [28,29], where a critical transition from a mixed phase space to a fully ergodic was found to cross a critical line t(a) = √ a 2 − 1. The E-C 3 B's classical dynamical properties will be studied in the same way but are characterized through the collisions of the orbits with the horizontal side of its FD shown in Fig.…”
Section: The Bi-parametric Billiards Families and Classical Dynamicssupporting
confidence: 91%
“…[28] showed that in the region a ∈ (1, √ 2) and t ∈ (0, ∞) are possible to find chaotic dynamics or a mixed phase space depending on the parameters. In [29] is presented a critical behavior of the billiard dynamics near a transition curve, t(a) = √ a 2 − 1 for the interval a ∈ (1, 4/3). Based on these previous works, we focus our analysis on this last interval and t ∈ (0, 1/ √ 3).…”
Section: The Bi-parametric Billiards Families and Classical Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations